2015
DOI: 10.1063/1.4935913
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between laser terahertz emission microscope and conventional methods for analysis of polycrystalline silicon solar cell

Abstract: A laser terahertz emission microscope (LTEM) can be used for noncontact inspection to detect the waveforms of photoinduced terahertz emissions from material devices. In this study, we experimentally compared the performance of LTEM with conventional analysis methods, e.g., electroluminescence (EL), photoluminescence (PL), and laser beam induced current (LBIC), as an inspection method for solar cells. The results showed that LTEM was more sensitive to the characteristics of the depletion layer of the polycrysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The THz waveforms monitored in the time domain include early-stage carrier dynamics information on a time scale of less than a picosecond. The dynamics-related information provided is different from that provided by typical photoluminescence, electroluminescence, and laser-induced photocurrent characterization methods [6]. We have reported several examples in which defect analysis [7], noncontact surface potential estimation [8,9], and nondestructive evaluation of solar cells [10] are demonstrated and shown that TES and LTEM are practical tools for semiconductor research and development.…”
Section: Introductionmentioning
confidence: 95%
“…The THz waveforms monitored in the time domain include early-stage carrier dynamics information on a time scale of less than a picosecond. The dynamics-related information provided is different from that provided by typical photoluminescence, electroluminescence, and laser-induced photocurrent characterization methods [6]. We have reported several examples in which defect analysis [7], noncontact surface potential estimation [8,9], and nondestructive evaluation of solar cells [10] are demonstrated and shown that TES and LTEM are practical tools for semiconductor research and development.…”
Section: Introductionmentioning
confidence: 95%
“…Nakanishi et al presented an LTEM as a tool for evaluating solar cells, where LTEM images are obtained by exciting a polycrystalline silicon solar cell with femtosecond laser illumination, visualizing the local distribution of the optical response, 47 and compared this LTEM method with conventional inspection methods in 2015. 48 Tonouchi 49 reviewed how LTEM is currently applied to solar wafer analysis in 2019.…”
Section: Advanced Solar Cellsmentioning
confidence: 99%
“…However, it lacked sufficient spatial resolution to examine individual cell devices. The LTEM technique (described above) was also employed to image and analyse solar cells [121,122,123]. Of particular interest is the detailed comparison of LTEM with conventional analysis methods, electroluminescence (EL), photoluminescence (PL), and laser beam induced current (LBIC) [123], which found that LTEM is a useful complementary technique that has advantages in spatial resolution and in its ability to observe electric fields, surface defects, grain boundaries, and photocarrier dynamics in the vicinity of the depletion layer.…”
Section: Electronicsmentioning
confidence: 99%